Compensation For Land Procurement For Klonengan Fly Over (FO) Development Project - Khoirunnisa, Nurizka Tiffany; Arpangi, Arpangi; Widayati, Widayati (Jurnal Konstatering, 2022)
Compensation for land acquisition has often been found in various areas where land has been affected by development projects for the public interest. One of the cases that occurred was in the Margasari area, Tegal Regency. The construction of the Fly Over project with Decision Number 05/Pdt.G/2017/PN.SLW which occurred on the Tegal-Pemalang-Pekalongan road section caused several problems, one of which was where the profit compensation was deemed unfair, so a lawsuit was filed in court. This study used a Juridical Empirical approach, by comparing the laws and regulations relating to disputes related to land acquisition for the public interest with practices that occur in the field through Decision Number 05/Pdt.G/2017/PN.SLW. Based on the results of research and discussion: 1) The land acquisition process carried out by the land acquisition committee in resolving disputes; 2) Achievement of the value of justice for communities affected by the Fly Over development project by comparing it with existing theories; 3) Implementation of compensation for land acquisition in accordance with the value of justice by comparing it with the principles contained in Act No. 2 of 2012. The conclusion from the writing of this law is that the compensation provided by the Government is fair and in accordance with existing and applicable regulations.